Pengembangan Kartu Urutan Berbasis Student-Centered Learning sebagai Media Pembelajaran Nilai Pancasila Kelas V SD - Indiyah Wungu Dari; Wahid Ibnu Zaman; Widi Wulansari (YASIN, 2026)
Although learning Pancasila values has become an important part of elementary education, studies that specifically develop Student-Centered Learning-based instructional media to help students understand and apply Pancasila values in daily life remain limited. In addition, the use of learning resources that are still dominated by textbooks and simple media has resulted in suboptimal student engagement in the learning process. This study aims to develop Student-Centered Learning-based Sequence Cards media that are valid, practical, and effective in teaching Pancasila values to fifth-grade elementary school students. This study used a Research and Development (R&D) approach with the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The study involved 28 fifth-grade students of SDN Mrican 2 in the limited trial and 29 fifth-grade students of SDN Mrican 1 in the wider trial. Data were collected through observation, interviews, documentation, questionnaires, and tests, and were then analyzed using Aiken’s V index, percentages of teacher and student responses, and N-Gain analysis. The results showed that the Sequence Cards media met the validity criteria based on expert validation results. The practicality of the media was in the very practical category, with a teacher response percentage of 100% and a student response percentage of 96%. The effectiveness of the media was indicated by an N-Gain score of 0.76 in the limited trial and 0.81 in the wider trial, both of which were in the high category. These findings contribute to the development of innovative Student-Centered Learning-based instructional media in Pancasila Education learning at the elementary school level. The conclusion of this study affirms that Sequence Cards media are feasible for use in increasing students’ active engagement and understanding of Pancasila values. The implications of this study provide alternative instructional media for teachers in creating more interactive, contextual, and student-centered learning, while also opening opportunities for further research on different materials and educational levels.